The Process of Nuclear Energy Generation as a Power Plant - Fauzan, Abd Rasyid Anhar; Hasanah, Annisa Nur; Pratama, Nurrahma; Ramba, Rezha Julyanti; Ningsih, Sri Rahayu Adi; Nur, Wahyuna (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
Nuclear energy has become a promising alternative in overcoming dependence on fossil fuels and improving energy efficiency. In this article, the author discusses the process of generating safe and environmentally friendly nuclear energy. Nuclear energy is produced through atomic nucleus reactions, such as nuclear fission, which create large amounts of energy. Nuclear reactors, such as nuclear power plants, utilize air as both a coolant and a moderator, generating electrical energy through a heat conversion process. The advantages of nuclear energy include its high energy density, better energy efficiency, and minimal greenhouse gas emissions. However, nuclear power plants also have disadvantages such as the risk of nuclear accidents and the high-level nuclear waste they produce. In summary, nuclear energy offers an effective solution for improving energy efficiency and reducing dependence on fossil fuels, but it must be balanced against its associated drawbacks and risks.